استعمال الطعم الجلدي الغضروفي (المركب) الأذني في ترميم جناح الأنف - ملحم فراس (Latakia University Journal -Medical Sciences Series, 2017)
تهدف عملية ترميم جناح الأنف إلى تحقيق نتائج شكلية جمالية من جهة ومن جهةٍ أخرى نتائج وظيفية. تكتسب الطعوم المركبة الأذنية أهميةً كبيرة هنا. الهدف من دراستنا هذه هو تقييم نتائج استخدام الطعوم المركبة في ترميم جناح الأنف. قمنا بدراسة استرجاعية لعشر حالات خضعت لترميم جناح الأنف باستخدام التكنيك المذكور بين عاميّ 2011 و2015 في مشفى الأسد الجامعي باللاذقية. كانت النتائج الشكلية والوظيفية لهذا التكنيك الجراحي البسيط نسبياً ممتازة. هذا التكنيك قادر على تأمين بطانة جيدة وهيكل داعم في آنٍ واحد. لقد استطعنا ملء العيب النسيجي باستعمال الطعم المركّب، ممّا أدّى إلى اختفاء العيب المذكور. الأمر الذي أحدث تحسّناً كبيراً في شكل الأنف بعد الجراحة. يمكن استعمال هذا التكنيك الفعال في ترميم بعض العيوب الماديّة الأنفية عبر مرحلةٍ واحدة. معدل الإمراضية بالنسبة للموقع المعطي كان منخفضاً جدّاً. بالنتيجة فإنّ الطعوم المركبة يمكنها أداء دورٍ هام كعامل مساعد للشرائح في عمليات ترميم الأنف. The reconstruction of the nasal ala requires the achievement of esthetic and functional results. Composite auricular grafts are extremely valuable here. The purpose of this study is to evaluate the surgical outcome after using composite grafts for alar nasal reconstruction according to our experience. A retrospective study of our outcome of 10 performed alar nasal reconstruction cases. All these patients were operated using the proposed surgical technique between 2011 and 2015 in AL-ASSAD University Hospital in Lattakia, Syria. The cosmetic and functional results of this relatively simple technique of reconstruction are excellent. It provides an internal lining and support. The integration was total. We could fill the alar nasal defect using composite grafts. The defect has disappeared consequently. The form of the nose could be improved. The use of this technique efficiently enables a one-stage reconstruction of nasal defects. The morbidity rate within the donor areas was low. We believe that composite grafts have an important and under-utilized role as an adjunct to the flaps in nasal reconstruction